Effect of U-shaped absorber tube on thermal-hydraulic performance and efficiency of two-fluid parabolic solar collector containing two-phase hybrid non-Newtonian nanofluids. (1st November 2020) - Yan, Shu-Rong; Golzar, Ali; Sharifpur, Mohsen; Meyer, Josua P; Liu, De-Hua; Afrand, Masoud
Highlights: Optimal geometry for parabolic solar collectors based on energy efficiency. Nanofluid effect on parabolic solar collectors using two-phase simulation. Eulerian-Eulerian method is employed to simulate two-phase nanofluid flow. Energy efficiency for the dual-pass pipe is higher than that of single-pass one. Abstract: In the present paper, the effect of U-shaped absorber tube on the performance of parabolic solar collector containing two-phase non-Newtonian nanofluids is studied numerically. The present study aims to obtain an optimal geometry for parabolic solar collectors based on energy efficiency. In this study, the effect of using nanofluid on parabolic solar collectors is investigated using two-phase simulation. The effect of Re number (2500<Re<5000), nanoparticle diameter (20np <50), volume fraction (1%<φ<4%) are investigated. The control volume method based on the SIMPLE algorithm is used to solve the governing equations. The Eulerian-Eulerian method is employed to simulate two-phase nanofluid flow. Surface-to-surface (S2S) is used for the simulation of the radiation and standard k-ε turbulence model is employed for modeling the turbulent equations. According to the results of the present work, the energy efficiency is always increasing with the Reynolds number for single-pass and dual-pass pipes. Hence, the optimal Reynolds number is 5000 where the highest energy efficiency occurs. It was also found that at all Reynolds numbers, the energy efficiency for the dual-pass pipe is higher than that of single-pass one. According to the results, in the case of the U-shaped system, the diameter of the pipe (assuming the hydraulic diameters are the same) is reduced, leading to an increase in the permeation of heat inside the passing flow, which is the reason for the enhancement of the efficiency. Graphical abstract: Image, graphical abstract